Pengaruh financial technology (fintech) adoption dan kepuasan pelanggan terhadap niat menggunakan kembali layanan e-commerce aplikasi shopee - Irfan, Muhamad; Suryanto, Suryanto; Dzulfikar, Irfan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of financial technology and customer satisfaction on the intention to reuse e-commerce services on the shopee application in the city of Bandung. this research was conducted with a quantitative approach to find cause-and-effect relationships (causality) between variables. The sample in this study were consumers who used online business applications as many as 100 respondents. The data collection technique in this study was to distribute questionnaires measured on a Likert scale to determine perceptions of questions regarding financial technology, customer satisfaction and intention to reuse e-commerce services. Multiple regression analysis was used in this study and then processed using the help of spss 23 for windows software. The results of this study indicate that financial technology and customer satisfaction have a significant influence on consumer intention to reuse e-commerce services on the shopee application. The findings of this study provide insights for practitioners, especially service providers, to understand the factors that can influence reuse intention so that it has a positive impact on sales growth.